1986
DOI: 10.1002/jcp.1041290102
|View full text |Cite
|
Sign up to set email alerts
|

Sodium 22+ washout from cultured rat cells

Abstract: The washout of Na+ isotopes from tissues and cells is quite complex and not well defined. To further gain insight into this process, we have studied 22Na+ washout from cultured Wistar rat skin fibroblasts and vascular smooth muscle cells (VSMCs). In these preparations, 22Na+ washout is described by a general three-exponential function. The exponential factor of the fastest component (k1) and the initial exchange rate constant (kie) of cultured fibroblasts decrease in magnitude in response to incubation in K+-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The details for the 2zNaf washout experiments are given elsewhere (Kino et al, 1986). Briefly, cells were loaded with 25 pCi/ml "Na+ for 2 hours.…”
Section: Na+ Washoutmentioning
confidence: 99%
“…The details for the 2zNaf washout experiments are given elsewhere (Kino et al, 1986). Briefly, cells were loaded with 25 pCi/ml "Na+ for 2 hours.…”
Section: Na+ Washoutmentioning
confidence: 99%
“…5 Briefly, cells in each well were washed twice with 5-ml aliquots of DMEM plus 10% FBS and loaded with 22 Na + in fresh medium for 20 minutes (20 /iCi/ml; Amersham, Arlington Heights, IL, US A) in the absence of ouabain and for 3 hours (8 /i.Ci/ml) in the presence of 10" 4 M ouabain. In preliminary studies we found that steady states with respect tô a" 1 " and Na + were attained at the indicated intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the largest and fastest of the three exponential components is likely to represent cellular Na+. This assertion is further substantiated by subsequent studies demonstrating that the exponential factor of the largest component is reduced by ouabain and is increased in a Ca2+-deficient medium (27). The exponential factor of the middle component was also sensitive to ouabain (27).…”
Section: Materials and Methods The Experimentsmentioning
confidence: 52%